Skrining Anemia terhadap Mahasiswa Teknologi Laboratorium Medis Poltekkes Kemenkes Jakarta III - Lestari, Puji; Astuti, Dewi; Maharani, Eva Ayu (Universitas Mohammad Husni Thamrin, 2024)
Anaemia is a symptom that can represent a person’s clinical condition. Several haematological parameters, Anaemia is a symptom that can represent a person’s clinical condition. Several haematological parameters, including Hb, erythrocytes, Ht, MCV, MCH, and MCHC, can be used as markkers of anaemia. Generally, anaemia is characterized by the condition of the body quickly becoming tired, weak, lethargic, dizzy and not energetic. This condition can interfere with activities, especially in the academic field. The aims of this study is to determine the incidence of anaemia in students. The descriptive observational study with a cross-sectional design was conducted at the Poltekkes Kemenkes Jakarta III haematology laboratory from March to October 2023. The respondents in this study were DIII Study Program and Applied Bachelor of the Department of Medical Laboratory Technology (TLM) totaled 304 students aged 18-21 years. All respondents signed an informed consent and took three cc volume of venous blood specimemens using EDTA tubes. The specimen was examined using the Sysmex BX-3010 Hematology Analyzer tool to obtain Hb, erythrocyte, Ht, MCV, MCH, and MCHC data. Based on the normal values used, the results of Hb, erythrocyte, Ht, MCV, MCH, and MCHC below normal values were 59 respondents (19,4%); 34 respondents (11,2%); 80 respondents (26,3%); 91 respondents (29,9%); 81 respondents (26,6%); dan 35 respondents (11,5%), respectively. Based on the haematological parameter data above, as many as 150 respondents (49,3%) were identified as having anaemia. It was concluded that based on the profile of complete blood tests, anemia still occurs quite a lot among students and needs attention and serious treatment. Key words: Anaemia, Haemoglobin, MCV, MCH, MCHC